M1 Protein Triggers a Phosphoinositide Cascade for Group A Streptococcus Invasion of Epithelial Cells - Purushothaman, Sai Sudha (American Society for Microbiology, 2003)
Invasion of nonphagocytic cells by bacteria provides a favorable niche for persistence and evasion of host defenses and antibiotics. M protein is a major virulence factor because it promotes high-frequency invasion of epithelial cells by group A Streptococcus (GAS) and also renders the bacterium resistant to phagocytosis. In this study, we investigated the role of M1 protein from serotype M1 strain 90-226 in regulating mammalian signal transduction and cytoskeletal rearrangement for bacterial entry. LY294002 and wortmannin, which are inhibitors of phosphatidylinositol 3-kinase (PI 3-K) blocked invasion of epithelial cells by GAS by 75 and 80%, respectively, but failed to inhibit invasion by Salmonella enterica serovar Typhimurium. Also, epithelial cells transiently transfected with dominant negative p85 and p110 genes, the regulatory and catalytic subunits of PI 3-K, respectively, were less able to be invaded by GAS. To separate the influence of other streptococcal virulence factors from M protein, Lactococcus lactis was engineered to express M1 protein on its surface. L. lactis(pLM1) invaded epithelial cells efficiently in vitro, and PI 3-K inhibitors blocked 90% of this invasion. Purified soluble M1 protein stimulated the formation of stress fibers and actin tuffs on epithelial cells. LY294002 and wortmannin inhibited these cellular changes. A phosphoinositide analogue also inhibited the invasion of epithelial cells by GAS. Therefore, M1 protein, either directly or via bound fibronectin, initiates signals that depend on the lipid kinase PI 3-K pathway, which paves the way for cytoskeletal rearrangement that internalize the bacterium.